The effects of some bis - 1, 2, 4 - Triazole containing aminomethyl derivatives on mda levels and vitamins in tissues of rats - Alayunt, Naci Omer; Karatepe, Mustafa; Parlak, Akif Evren; Ulas, Mustafa; Turkoglu, Semra; Dastan, Sevgi Durna; Celik, Sait (Chemical Society of Pakistan, 2019)
Summary: It was reported that the 1, 2, 4-triazole and the derivatives of this compound demonstrate numerous activities in a pharmacological point of view. 1, 2, 4-Triazole moieties were employed in an extensive range of drug candidates, which are therapeutically promising and include anti-inflammatories, anti-anxiety compounds, sedatives, CNS stimulants, antimicrobial agents, and antimycotic ones such as intraconazole, fluconazole and voriconazole. In the current investigation, several aminomethyl derivatives, which contain bis-1, 2, 4-triazole, were newly synthesized and their impacts on the levels of antioxidant vitamins (A, C and E) and malondialdehyde (MDA) were examined in serum, kidney and liver of rats. The investigation of the levels of the vitamins (A, C and E) and malondialdehyde (MDA) were performed by calculations in HPLC system. In the study, the observed antioxidant activity revealed that all the analyzed compounds, have promising antioxidant activities, which may be the result of the presence of benzylpiperazine and dipropylamine, and a methylpiperidine moiety as well as the allyl group. Therefore, it was concluded that ample scope exists for further studies. © 2019 Chemical Society of Pakistan. All rights reserved.
Keywords: 1,2,4 - triazole; Aminomethyl derivatives; Kidney; Liver; Malondialdehyde (A, E and C) Vitamins